Hepatitis B surface antigen hijacks TANK-binding kinase 1 to suppress type I interferon and induce early autophagy - Chuanjin Luo; Caijiao Ma; Gang Xu; Chengbo Lu; June Ma; Yu Huang; Longyu Nie; Chen Yu; Yongfang Xia; Zhiqiang Liu; Ying Zhu; Shi Liu (Cell Death and Disease)
Abstract There are close links between innate immunity and autophagy. However, the crosstalk between innate immunity and autophagy in host cells infected with hepatitis B virus (HBV) remains unclear. Here, we reported that HBsAg suppressed type I interferon production and induced the accumulation of autophagosomes. HBsAg boosted TANK-binding kinase 1 (TBK1) phosphorylation and depressed interferon regulatory factor 3 (IRF3) phosphorylation ex vivo and in vivo. Mechanistic studies showed that HBsAg interaction with the kinase domain (KD) of TBK1 augmented its dimerization but disrupted TBK1–IRF3 complexes. Using the TBK1 inhibitor, BX795, we discovered that HBsAg-enhanced TBK1 dimerization, promoting sequestosome-1 (p62) phosphorylation, was necessary for HBV-induced autophagy and HBV replication. Moreover, HBsAg blocked autophagosome–lysosome fusion by inhibiting the synaptosomal-associated protein 29 (SNAP29) promoter. Notably, liver tissues from HBsAg transgenic mice or chronic HBV patients revealed that IFNβ signaling was inhibited and incomplete autophagy was induced. These findings suggest a novel mechanism by which HBsAg targets TBK1 to inhibit type I interferon and induce early autophagy, possibly leading to persistent HBV infection. Molecular mechanisms of HBsAg suppression of the IFNβ signaling pathway and triggering of early autophagy. HBsAg targets the kinase domain of TBK1, thereby disrupting the TBK1–IRF3 complex and inhibiting type I interferon production. On the other hand, HBsAg enhances TBK1 dimerization and phosphorylation, which upregulates the phosphorylation of p62 to induce p62-mediated autophagy. Furthermore, HBV infection causes the accumulation of autophagosomes. This is achieved by HBsAg suppressing the SNAP29 promoter activity, which blocks autophagosome–lysosome fusion.